Mengoptimalkan Return: Menganalisis Dampak Kurs, Book Value per Share, dan Earning per Share - Arianingtias, Desti Dwirahayu; Dura, Justita (Jurnal Ekonomi Akuntansi dan Manajemen, 2024)
This research aims to determine the effect of the Exchange Rate, Book Value per Share, and Earnings per Share on Stock Returns in the transportation sector listed on the IDX for the period 2020 to 2023. The dependent variable in this research is stock returns, while the independent variables consist of exchange rate, Book Value per Share, and Earnings per Share. The sampling technique in this research was using a purposive sampling method. From 2020 to 2023 of the transportation and logistics companies listed on the Indonesia Stock Exchange during the research period, only 16 companies were eligible to be used as samples for this research. The data was tested using Eviews version 12 by testing classical assumptions with the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Data analysis used multiple linear regression analysis tests and hypothesis testing using the coefficient of determination analysis test (RÂ²) and t test. The research results show that only the variables Exchange Rate, Book Value per Share, Earning Per Share have no effect on stock returns of transportation and logistics companies listed on the Indonesia Stock Exchange (BEI). Keywords: Kurs, Book Value per Share, Earning per Share, Return Saham